ФОРМЫ РЕАЛИЗАЦИИ ПРАВА КОМУНАЛЬНОЙ СОБСТВЕННОСТИ - Соловей, Наталья Сергеевна (SUPREMANCE OF LAW, 2016)
The article discusses the realization forms of communal ownership. The concept of the right and its forms. The characteristics of the individual forms of realization of municipal property. Highlighted the problems that arise in the implementation of this law. Established the principles to be met by the mechanism of realization of municipal property.